The Social Importance of the Bogomil Movement in the Light of the Sermon by Cosmas the Priest. Source Facts and Historiographical Speculations, an Attempt at Assessment - Wolski, Jan (Vox Patrum, 2026)
The social significance of the Bogomil movement in its earliest phase has been the subject of much analysis in the academic literature. Despite the poor source base, many hypotheses have been formulated in this regard. By reaching out to the primary studies of the topic, I attempt to trace the reasoning presented in them and assess the quality of the arguments used. Most of the claims concerning the social significance of Bogomilism turn out to be detached from the sources.